Voyages to the stars and galaxies - Fraknoi, Andrew; Morrison, David; Wolff, Sidney (Australia, Thomson, 2004)
VOYAGES TO THE STARS AND GALAXIES provides students and professors with the ideal combination of authors and experience. It is written by an award-winning astronomy educator (Fraknoi) and two distinguished research scientists (Morrison at NASA and Wolff at NOAO). This author team combines the latest science with classroom-tested teaching strategies and a student-friendly approach. Through unique group activities and a focus on astronomy as a human endeavor, the authors engage and involve students, helping them both understand and enjoy astronomy. The market-leading technology package includes access to InfoTrac(R)College Edition (free!) and TheSky(t) Student Edition CD-ROM (free!), as well as an optional package with the RedShift(t) College Edition CD-ROM (including animations) along with an accompanying workbook.
Appendix 1-15, 522-559p.; Index 562-573p.
Keywords: Astronomy; Star; Mathematics